Analisis Pengaruh Deteksi Dini Kecurangan Laporan Keuangan Dengan Gender sebagai Variabel Moderating - Yudieth Bian Sabatina; Agus Wahyudin (Universitas Katolik Soegijapranata Semarang, 2021)
This study examines the impact of audit quality, auditor experience, and professional skepticism on early detection of financial statement with gender as the moderating variable. Using non-random sampling, as much as 55 respondents were collected from externl auditors in Semarang, Indonesia. The results indicate that audit quality has a significant positive effect on early detection of financial statements. Meanwhile, the auditor experiences and professional skepticism have no significant effect on early detection of financial statements. As for moderating variable, results show that gender does not moderate the effect of independent variables on early detection of financial statements. Based on the results found in this study, audit firms are suggested to be able to provide sufficient training and facilities for auditors in order to provide good audit quality, auditors are expected to carry out every audit process well so can produce good audit quality, and the future researches is expected to take a wider population range and research samples in order to get a larger and more diverse sample.